Psikologi komunitas: Peran psikologi komunitas terhadap kebijakan kesehatan mental - Utomo, Adi Tri Minto (Maliki Interdisciplinary Journal, 2024)
The concept of mental health policy represents a structured framework designed to attain the overall well-being of the populace in Indonesia. Nevertheless, these policies pertaining to mental health haven't gained sufficient traction within the Indonesian public. Moreover, the availability of skilled professionals adept at handling mental health concerns stands in inverse proportion to the extensive Indonesian population. This particular reality significantly impacts the evolution of mental health protocols within the country. A potential remedy to enhance mental health nationwide involves implementing broad-scale treatment initiatives, starting within the community and subsequently extending to personalized care. The primary objective of community psychology revolves around tackling prevailing issues within a given society or communal setting. Predicaments existing within these spheres will be effectively addressed through well-planned and innovative social interventions, manifesting as community-oriented service endeavors and progressive developmental programs. The methodology employed within this manuscript employs a literature review strategy to delve into both mental health policy and the pivotal role of community psychology. The conclusions drawn from this exposition underscore the instrumental role of community psychology in fostering the prosperity and contentment of individual Indonesians, thereby lending support to the overarching mental health policies within Indonesian society. Keywords: Mental Health, Mental Health Policy, Community Psychology